Variables associated with patient activation in persons with multiple sclerosis. (January 2016) - Goodworth, Marie-Christine R; Stepleman, Lara; Hibbard, Judith; Johns, Lisa; Wright, Dustin; Hughes, Mary D; Williams, Mitzi J
Identifying variables associated with patient activation in the multiple sclerosis population could serve to facilitate better multiple sclerosis self-management behaviors. Using a cross-sectional survey design, 199 participants were recruited from a multiple sclerosis center in the Southeastern United States. Depression, multiple sclerosis quality of life, and multiple Sclerosis self-efficacy were all significantly correlated with patient activation. Results of a hierarchical regression indicated that patient activation was significantly related to educational attainment, depression, and self-efficacy but not to quality of life. The results suggest several possible targets for intervention to increase patient activation, including health literacy, depression symptoms, and self-efficacy for multiple sclerosis disease management.